2015
DOI: 10.1128/jb.00337-15
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms Found in the migA and wbpX Glycosyltransferase Genes Account for the Intrinsic Lipopolysaccharide Defects Exhibited by Pseudomonas aeruginosa PA14

Abstract: Pseudomonas aeruginosa PA14 is widely used by researchers in many laboratories because of its enhanced virulence over strain PAO1 in a wide range of hosts. Although lipopolysaccharide (LPS) is an important virulence factor of all P. aeruginosa strains, the LPS of PA14 has not been characterized fully. A recent study showed that the structure of its O-specific antigen (OSA) belongs to serotype O19. We found that the OSA gene cluster of PA14 shares ϳ99% identity with those of the O10/O19 group. These two serotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Between 16 h and 48 h of biofilm growth, the density of cells and exopolysaccharides was gradually reduced, suggesting a defect in biofilm maturation [107]. These results were substantiated in another study that observed the restoration of biofilm maturation when CPA synthesis was rescued in a CPA-deficient isolate, PA14 [130]. The importance of CPA in biofilms is also demonstrated by its link to the secondary messenger cyclic-di-GMP, the so-called "master regulator", that induces the physiological changes necessary to switch from motile planktonic growth to sessile biofilm growth.…”
Section: The Role Of Lps In Planktonic and Biofilm Modes Of Growthmentioning
confidence: 54%
“…Between 16 h and 48 h of biofilm growth, the density of cells and exopolysaccharides was gradually reduced, suggesting a defect in biofilm maturation [107]. These results were substantiated in another study that observed the restoration of biofilm maturation when CPA synthesis was rescued in a CPA-deficient isolate, PA14 [130]. The importance of CPA in biofilms is also demonstrated by its link to the secondary messenger cyclic-di-GMP, the so-called "master regulator", that induces the physiological changes necessary to switch from motile planktonic growth to sessile biofilm growth.…”
Section: The Role Of Lps In Planktonic and Biofilm Modes Of Growthmentioning
confidence: 54%
“…Therefore, elevated ROS production in response to treated Psl-producing strains is likely a result of increased complement deposition. As previously demonstrated, differences in the structure of lipopolysaccharides (LPS) produced by PA14 result in increased sensitivity to a variety of factors, relative to PAO1 (34). Due to increased serum sensitivity, we were unable to determine the effect of hydrolase treatment on the phagocytosis of PA14 and CF127, but we were able to measure the ROS response.…”
Section: Figmentioning
confidence: 89%
“…These data indicate that reduction of CPA LPS after acquisition of PAP1-1 serves as an exclusion mechanism for acquisition of multiple copies of the PAPI-1 island. It is worth noting that PA14 strain contains a SNP in the CPA biosynthesis gene wbpX and naturally does not produce CPA [ 60 ]. In fact, in accordance with our proposed role of the reduction of CPA as an exclusion mechanism, we found that the EI value for mating between PA14 donor and PA14+ recipient was 12, which is an order of magnitude lower than that measured for PAO1.…”
Section: Discussionmentioning
confidence: 99%